El sicariato como delito típico debería incorporarse al código penal Ecuatoriano. - Calvache Ponce, José Eduardo (2011)
The final formless present of thesis titles "THE SICARIATO LIKE TYPICAL CRIME should INCORPORATE TO THE ECUADORIAN PENAL CODE" Today per today the sicariato is one of the phenomena but grades that is affecting from a direct way to the guarantees and right constitutional like they are the right to the life and the personal integrity given in the Art. 66 numeral 1 and 3 of the Constitution of the Republic of the Ecuador. This pregrado thesis seeks to expose and to demonstrate that the right to the life has been harmed and forced by new criminal forms as the sicariato in our other country; a that tipificado is not properly and sanctioned in the Penal Code, being applied similar norms by homicide or murder to the moment to judge the responsible of the infraction. The sicariato is a very interesting topic and that to be treated to depth an important storing it is required, so much in its artificial and doctrinal argument for the foundation of the crime like autonomous criminal figure, as much as in its verification like social problem through the field investigation Also understands a historical study of its evolution and a study compared with legislations that contemplate it. In definitive this work converges toward the incorporation of the crime of Sicariato in the Ecuadorian Penal Code, and that this way you can replace the hole in what corresponds to its tipificación like autonomous crime.